Hemosiderotic Dermatofibroma: An Interesting Case When Pigments Blur the Diagnostic Path - Tanmayi V. Kulkarni; Ruchika M. Chamaria; Archana C. Buch; Sushama G. Gurwale (Medical Journal of Dr. D.Y. Patil Vidyapeeth)
Hemosiderotic dermatofibroma is a rare variant of dermatofibroma. Due to its brown nodular presentation, it mimics melanotic lesions. A definite diagnosis is essential for proper management and prognosis. We present one such rare case of 49-year-old male where histopathology with special stains and immunohistochemistry helped to solve the dilemma.